Case Report: Internal Carotid Artery Thrombosis: A Rare Complication After Fibrin Glue Injection for Cavernous Sinus Hemostasis - Andrade-Barazarte, Hugo; Chen, Zhongcan; Feng, Chenyi; Srinivasan, Visish M.; Furey, Charuta G.; Lawton, Michael T.; Hernesniemi, Juha (Frontiers in Surgery, 2021)
Background: Fibrin glue injection within the cavernous sinus (CS) is a demonstrably safe and simple technique to control venous bleeding with a low complication rate. However, this technique does have inherent risks. We illustrate 2 cases of internal carotid artery (ICA) thrombosis after fibrin glue injection in the CS for hemostasis. Methods: After encountering this complication recently, we conducted a retrospective review of the surgical database of 2 senior neurosurgeons who specialize in cerebrovascular and skull base surgery to identify patients with any complications associated with the use of fibrin glue injection for hemostasis. Approval was given by respective institutional review boards, and patient consent was obtained. Results: Of more than 10,000 microsurgery procedures performed by 2 senior neurosurgeons with a combined experience of 40 years, including procedures for aneurysms and skull base tumors, 2 cases were identified involving ICA thrombosis after fibrin glue injection in the CS for hemostasis. Both cases involved severe ischemic complications as a result of the ICA thrombosis. In this article, we present their clinical presentation, characteristics, management, and outcomes. Conclusion: Direct injection of fibrin glue into the CS for hemostasis can effectively control venous bleeding and facilitate complex dissections. However, it can be associated with ICA thrombosis, with subsequent serious ischemia and poor prognosis. Although this complication appears to be rare, increased awareness of this problem should temper the routine use of fibrin glue in anterior clinoidectomy and transcavernous approaches.